Penerapan Model Poblem Possing Untuk Meningkatkan Minat Belajar Akutansi Siswa Kelas X SMK - nuraini nuraini; Sudjarwo Sudjarwo; Pargito Pargito (Faculty of Teacher Training and Education, University of Lampung, 2018)
The purpose of this research is to know the interest and the result of the students’ accounting cognitive learning by using problem posing learning model. This research is an action research. The activity of this research was conducted a number of three cycles. The subject of this research was the students’ of accounting tenth grade SMK a number 35 students. The data collecting technique used observation learning activity sheet with seven indicators of success namely The data of observation result and formative test on each cycle become the basic or repair material on the next cycle. The result of research show that : there is improvement of learning interest and result of the students’ cognitive learning on each cycle. After using model in learning problem posing accounting subject. Penelitian ini bertujuan untuk mengetahui minat dan hasil belajar kognitif Akutansi siswa dengan menggunakan model pembelajaran Problem Posing. Kegiatan penelitian ini dilaksanakan sebanyak tiga siklus. Subjek penelitian adalah seluruh siswa di kelas X Akutansi SMK sebanyak 35 siswa. Alat pengumpulan data menggunakan lembar pengamatan aktivitas belajar dengan 10 indikator keberhasilan. Data dari hasil observasi dan tes formatif pada setiap siklus menjadi dasar atau bahan perbaikan pada siklus berikutnya. Hasil penelitian menunjukkan bahwa: terdapat peningkatan minat belajar dan hasil belajar kognitif siswa disetiap siklus.Kata Kunci : Minat belajar, akuntansi, problem posing.